A case of mumps conjunctivitis: Detection of the virus RNA by nested PCR in tear sample - Kalkan, A; Ozden, M; Yilmaz, T; Demirdag, K; Bulut, Y; Ozdarendeli, A (Informa Healthcare, 2004)
Mumps is a disease caused by a virus that can infect many parts of the body, especially the parotid salivary glands. A case of epidemic parotitis in an adult female affected by bilateral conjunctivitis is presented. Mumps virus was detected in tear samples by reverse transcription nested polymerase chain reaction (RT-n-PCR). The conjunctivitis resolved completely within 11 d.
Keywords: Rapid Detection